Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
bài 1:
a) x(x-2)-5y-(x-2)=(x-5y)(x-2)
b) =(2x-3-4x)(2x-3+4x)=(-2x-3)(6x-3)
bài 2 bạn tự luyện nhé
b)4x^2y^2-(x^2+y^2)^2
=(2xy)2-(x2+y2)2
=[2xy-(x2+y2)][2xy+(x2+y2)]
=(2xy-x2-y2)(2xy+x2+y2)
=-(-2xy+x2+y2)(x+y)2
=-(x-y)2(x+y)2
c) x^2+2x-3
=x2-x+3x-3
=x(x-1)+3(x-1)
=(x-1)(x+3)
d) 2a^3-54b^3
=2(a3-27b3)
=2[a3-(3b)3]
=2(a-3b)(a2+3ab+9b2)
a: \(ab+a+b+1\)
\(=a\left(b+1\right)+\left(b+1\right)\)
\(=\left(b+1\right)\left(a+1\right)\)
c: \(4x^2-12xy+3x-9y\)
\(=4x\left(x-3y\right)+3\left(x-3y\right)\)
\(=\left(x-3y\right)\left(4x+3\right)\)
a) \(2x+2y=2\left(x+y\right)\)
b) \(4ab-10a=2a\left(2b-5\right)\)
c) \(\left(x^2+1\right)^2-4x^2=\left(x^4+2x^2+1\right)-4x^2=\left(x^2-1\right)^2\)